2015
DOI: 10.1177/0269881115598415
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of MDPV in rat striatum correlate with the psychostimulant effect

Abstract: 3,4-methylenedioxypyrovalerone or MDPV is a synthetic cathinone with psychostimulant properties more potent than cocaine. We quantified this drug in the striatum after subcutaneous administration to rats. MDPV reached the brain around 5 min after its administration and peaked at 20-25 min later. The elimination half-life in the striatum (61 min) correlates with the decrease in the psychostimulant effect after 60 min. Around 11% of the administered dose reached the striatum and, considering a homogeneous brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 34 publications
10
56
0
Order By: Relevance
“…These results suggest that the central mechanisms of the locomotor stimulant actions of MDPV at least partly involve dopaminergic stimulation, which was attenuated by cis-flupenthixol pretreatment. These results are consistent with a recent study showing that MDPV stimulated locomotor activity at the same doses and administration routes used in the present work (Novellas et al, 2015). Novellas et al (2015) found that pretreatment with haloperidol, an antagonist for dopamine and other amine neurotransmitter receptors, 10 min before MDPV administration completely blocked the locomotor stimulant actions of MDPV.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These results suggest that the central mechanisms of the locomotor stimulant actions of MDPV at least partly involve dopaminergic stimulation, which was attenuated by cis-flupenthixol pretreatment. These results are consistent with a recent study showing that MDPV stimulated locomotor activity at the same doses and administration routes used in the present work (Novellas et al, 2015). Novellas et al (2015) found that pretreatment with haloperidol, an antagonist for dopamine and other amine neurotransmitter receptors, 10 min before MDPV administration completely blocked the locomotor stimulant actions of MDPV.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with a recent study showing that MDPV stimulated locomotor activity at the same doses and administration routes used in the present work (Novellas et al, 2015). Novellas et al (2015) found that pretreatment with haloperidol, an antagonist for dopamine and other amine neurotransmitter receptors, 10 min before MDPV administration completely blocked the locomotor stimulant actions of MDPV. When compared with the present partial effects of the more selective dopamine receptor blocker, this might suggest that other neurotransmitter systems are involved in MDPV's potent stimulant actions.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The attenuation of locomotor response by SCH23390 confirms the mechanistic involvement of D1-like receptors. SCH23390 has been previously shown to block expression of MA-, mephedrone-, and cocaine-induced hyperactivity in rodents after injection (Hall et al, 2009;Lisek et al, 2012;Rauhut, 2015;Schindler and Carmona, 2002), and MDPV-induced hyperactivity has also been shown to be mediated through a dopamine receptordependent mechanism (Marusich et al, 2014;Novellas et al, 2015). Our findings demonstrate that an increase in locomotor activity induced by the inhalation of MA, MDPV, and mephedrone is similarly mediated by a D1-like receptordependent mechanism.…”
Section: Discussionsupporting
confidence: 64%